CRISPR/CAS9 Technologies. (23rd February 2017) - Williams, Bart O; Warman, Matthew L
ABSTRACT: The Clustered Regularly Interspaced Palindromic Repeats (CRISPR)/CRISPR‐associated protein (Cas) pathway is revolutionizing biological research. Modifications to this primitive prokaryotic immune system now enable scientists to efficiently edit DNA or modulate gene expression in living eukaryotic cells and organisms. Thus, many laboratories can now perform important experiments that previously were considered scientifically risky or too costly. Here, we describe the components of the CRISPR/Cas system that have been engineered for use in eukaryotes. We also explain how this system can be used to genetically modify cell lines and model organisms, or regulate gene expression in order to search for new participants in biological pathways. © 2017 American Society for Bone and Mineral Research.